2016
DOI: 10.3233/wor-162388
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social status among people with psychiatric disabilities attending work-oriented and meeting place-oriented day centers

Abstract: BACKGROUND: Day centers have been criticized for giving attendees a lower social status

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…This has previously been shown for various aspects of occupation among people with mental health problems, such as occupational engagement [33] and the value linked with one's everyday occupations [34]. Self-mastery has also been found to be important for perceived social status among people with psychiatric disabilities [35] and to be associated with less severe basic needs in this group [36]. This significance concerning self-mastery warrants consideration of how to support self-determination as far as possible in the housing support context, particularly since research has shown that being deprived of selfdetermination tends to be a major concern for people living in SH [37].…”
Section: Discussionmentioning
confidence: 82%
“…This has previously been shown for various aspects of occupation among people with mental health problems, such as occupational engagement [33] and the value linked with one's everyday occupations [34]. Self-mastery has also been found to be important for perceived social status among people with psychiatric disabilities [35] and to be associated with less severe basic needs in this group [36]. This significance concerning self-mastery warrants consideration of how to support self-determination as far as possible in the housing support context, particularly since research has shown that being deprived of selfdetermination tends to be a major concern for people living in SH [37].…”
Section: Discussionmentioning
confidence: 82%